How Young Leaders' Social Media Strategies Shape Public Emotion: A Systematic Literature Review - Syibly Adam Firmanda; Reza Fathurrahman (Dinasti International Journal of Education Management And Social Science, 2025)
This study investigates how young leaders utilize social media as a strategic communication tool to influence public emotion within digital political environments. Employing a Systematic Literature Review (SLR) approach and guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, 15 peer-reviewed journal articles published between 2015 and 2024 were critically reviewed. The findings are categorized into four major themes: political engagement, emotional mobilization, public trust, and crisis communication. The analysis reveals that young leaders strategically use emotional narratives such as anger, hope, fear, and solidarity to shape public sentiment, mobilize action, and foster trust, especially during times of sociopolitical unrest and public health crises. Additionally, the study emphasizes the challenges posed by disinformation and the importance of authenticity, emotional tone, and adaptive messaging in digital leadership. This research contributes to the discourse on youth political communication by proposing the need for emotion-centered strategic frameworks to guide impactful and responsible social media engagement.